Study of the performance of organic solar cells using SnO2 nanoparticles as electron transport layer growth by pulsed laser deposition - Faris M.A. Al-Hamdany; Abdulkhaliq A. Sulaiman; Abdullah I.M. Alabdullah (Хімія, фізика та технологія поверхні, 2024)
The electron transport layer (ETL) material plays a crucial role in determining the device efficiency and stability of organic solar cells (OSCs). Tin oxide (SnO2) semiconductor is commonly used as ETL in organic solar cells and recently has attracted significant attention. In this paper SnO2 particles deposited by pulsed laser deposition (PLD) are used as ETL layer in inverted organic solar cells with structure (FTO/SnO2/PTB7-Th:O-IDTBR/ MoO3/Ag). The characterizations of cell using the Ossila Solar Cell I-V Test System have been investigated as well as the structural properties of SnO2 thin film using a Field emission scanning electron microscope (FESEM), The atomic force microscopy (AFM) and X-ray spectrum have been also investigated. It has been found that the Power conversion efficiency (PCE) of solar cell is 15.08 %. The stability was measured for 30 min with continuous illumination under the ambient air conditions, it was decreasing gradually over the illumination period to about half initial value of efficiency. The FESEM images and XRD spectrum show that the films were crystalline. The XRD spectrum shows the presence of several peaks belonging to SnO2 nanoparticles. The optical properties of SnO2 film indicate the increase in the transmittance and refractive index spectrum, while the absorbance spectrum decreases, the maximum absorbance was observed at 320 nm wavelength and the optical energy gap record about 3.1 eV and the grain size for SnO2 reported around 20–60 nm.